2019
DOI: 10.3390/ijerph16152805
|View full text |Cite
|
Sign up to set email alerts
|

Cd, Cu, and Zn Accumulations Caused by Long-Term Fertilization in Greenhouse Soils and Their Potential Risk Assessment

Abstract: The intense management practices in greenhouse production may lead to heavy metal (HM) accumulations in soils. To determine the accumulation characteristics of HM and to evaluate possible HM sources in greenhouse soils, thirty typical greenhouse soil samples were collected in Shouguang District, Shandong Province, China. The results indicate that the Cd, Cu, and Zn concentrations are, respectively, 164.8%, 78.6%, and 123.9% higher than their background values. In the study area, Cd exhibits certain characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 61 publications
1
9
1
Order By: Relevance
“…The result obtained for the non-alcoholic drinks were totally in conformance with the standard maximum limit (0.055 ppm). The incidences of cadmium contaminations are mostly from industrial activity, air readily taken up by plants, water used for irrigation, smoking and or the presence of cadmium in fertilizers (Liao et al, 2019). Our study findings indicate Cd levels lower than those of a study obtained by Iwegbue et al (2014) who observed mean concentrations of 0.01 to 0.04 μg/mL while Okareh et al (2018) observed Cd levels ranging from 60 to 70 µg/L in distilled alcoholic beverages and liquors in Nigeria.…”
Section: Observed Meancontrasting
confidence: 68%
“…The result obtained for the non-alcoholic drinks were totally in conformance with the standard maximum limit (0.055 ppm). The incidences of cadmium contaminations are mostly from industrial activity, air readily taken up by plants, water used for irrigation, smoking and or the presence of cadmium in fertilizers (Liao et al, 2019). Our study findings indicate Cd levels lower than those of a study obtained by Iwegbue et al (2014) who observed mean concentrations of 0.01 to 0.04 μg/mL while Okareh et al (2018) observed Cd levels ranging from 60 to 70 µg/L in distilled alcoholic beverages and liquors in Nigeria.…”
Section: Observed Meancontrasting
confidence: 68%
“…Increasing Zn concentration during second sampling dates within greenhouse soil was noticed to be higher, which were closely related to the pollutants in irrigation water especially during using wastewater directly for irrigation, agricultural soil fertilizers, and used pesticides. These results are in accordance with recent studies (44,22). Although an enrichment of soils with Zn has been reported when these materials were used during long-term repeated additions, after the abandonment of agricultural applications and remaining trace metals in the soil (30).…”
Section: Resultssupporting
confidence: 92%
“…The concentration of Cr in the greenhouse soils exceed the concentrations in the background soils, which, indicated that greenhouse cultivation and application of pesticides and livestock manure had a significant effect on the concentrations of Cr in irrigated soil (5). Recent study reported that parent rocks mainly determine Cr concentrations in greenhouse soil fields (22). The total Ni concentration in studied soil was ranged between (181.1±3.14 to 187±3.39 g/kg), the highest value was (214 g/kg) recorded during September at site 7, and the lowest value recorded (155 g/kg) in site 9 during March (Figure 7).…”
Section: Resultsmentioning
confidence: 77%
“…In the PCA, the eigenvalues and variances were determined to establish principal components (PCs). With PCA diagrams, it is possible to observe the interaction between the variables and samples; a grouping of samples suggests a common source [52].…”
Section: Hydrogeochemical Analysismentioning
confidence: 99%